Staged Hybrid Techniques With Straightforward Bypass Surgery Followed by Flow Diverter Deployment for Complex Recurrent Middle Cerebral Artery Aneurysms - Tanabe, Jun; Nakahara, Ichiro; Matsumoto, Shoji; Morioka, Jun; Hasebe, Akiko; Watanabe, Sadayoshi; Suyama, Kenichiro; Kuwahara, Kiyonori (Frontiers in Surgery, 2022)
Background: Recurrent complex middle cerebral artery (MCA) aneurysms after combined clipping and endovascular surgery are challenging, and if conventional techniques are adapted, advanced surgical, endovascular, and a combination of both techniques are often required. For such complex aneurysms, safe and effective straightforward techniques for all neurovascular surgeons are warranted. We describe the details of staged hybrid techniques with straightforward bypass surgery followed by flow diverter deployment in a patient with a complex MCA aneurysm. Illustrative case: A 69-year-old woman presented with left recurrent large MCA aneurysm enlargement 25 years after direct surgery and coil embolization for a ruptured aneurysm. The recurrent MCA aneurysm had a large and complex morphology and was adhering to the brain tissues. Therefore, it was unsuitable to treat such aneurysm with conventional surgical and endovascular techniques with a high risk of morbidity. We performed (1) M2 ligation following superficial temporal artery-M2 bypass and (2) flow diverter deployment assisted with coil packing in two sessions. Three months after the second session, the aneurysm was completely occluded with endothelialization of the neck. Angiographic findings revealed no recurrence 12 months after the treatment. Conclusions: Staged hybrid techniques with straightforward bypass surgery followed by flow diverter deployment may be a safe and effective treatment for complex recurrent MCA aneurysms.